2014
DOI: 10.1007/s10151-014-1146-8
|View full text |Cite
|
Sign up to set email alerts
|

A laparoscopic approach to benign retrorectal tumors

Abstract: In our experience, a laparoscopic approach is safe for removing benign tumors in the retrorectal space. This approach may provide access to this difficult-to-reach space and has the advantages of allowing excellent visualization, meticulous dissection, less morbidities, and fast recuperation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 39 publications
2
14
0
Order By: Relevance
“…We identified quite 20 previous cases of pelvic schwannomas removed by laparoscopy or robotic surgery. Retrorectal and obturatory space are the location more often involved [ [5] , [6] , [7] , [11] , [12] , [13] ] while schwannoma of lateral pelvic space are described in only four case report [ [3] , [4] , [14] , [15] ]. Here we report a case of laparoscopic extirpation of a large pelvic schwannoma arising from the hypogastric plexus in an obese man.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We identified quite 20 previous cases of pelvic schwannomas removed by laparoscopy or robotic surgery. Retrorectal and obturatory space are the location more often involved [ [5] , [6] , [7] , [11] , [12] , [13] ] while schwannoma of lateral pelvic space are described in only four case report [ [3] , [4] , [14] , [15] ]. Here we report a case of laparoscopic extirpation of a large pelvic schwannoma arising from the hypogastric plexus in an obese man.…”
Section: Discussionmentioning
confidence: 99%
“…First laparoscopic resection of a pelvic schwannoma has been reported in 1996 by Melvin [ 2 ]. From this report, only few other laparoscopic removal of such neoplasms has been described [ [3] , [4] , [5] , [6] , [7] ].…”
Section: Introductionmentioning
confidence: 99%
“…Nedelcu et al recommended a laparoscopic approach only for tumors <6 cm diameter based on a case of a 7-cm schwannoma that required open conversion because of its large size (5). In contrast, Fong et al reported a 15-cm schwannoma successfully resected using a laparoscopic approach (3), and Zhou et al used a laparoscopic approach irrespective of tumor size (6). We successfully excised RT >9 cm in diameter laparoscopically in cases 1 and 2, in which visualization of the dissection site was possible by dissecting the tumor from the pelvis.…”
Section: Discussionmentioning
confidence: 99%
“…The conventional surgical approach is transabdominal, transperineal, or combined, depending on the location and anatomical features of the tumor (2). Recently, a successful laparoscopic approach for RT reported good cosmesis, good visualization of the deep retrorectal space, and a good postoperative course (3)(4)(5)(6)(7)(8). However, three cases of open conversion have also been reported (4,5), and the indication for this approach is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The lesions are susceptible to infection, development into a fistula, or malignant transformation. Compression of surrounding structures such as the rectum, development of symptoms (constipation, lower abdominal pain, and dysuria), and features hinting a malignant transformation are indications of surgery, which remains the best treatment option [5].…”
Section: Introductionmentioning
confidence: 99%